Origin of Widmanstatten Microstructure in Homogenized Ag-Sn Dental Alloys - Harsono Wirjosumarto; Richard S. Mateer (Institute for Research and Community Services (LPPM) ITB, 1976)
Abstract. Widmanstatten microstructures are often observed in Ag-Sn dental alloys, after they underwent slow cooling for homogenization temperature. This structure appears when the alloy contains silver or silver equivalent between 75 and 80 wt %. Hatchet mark structure somewhat similar to Widmanstatten structure may be generated during the metallographic preparation of the specimens. These marks are actually mechanical twins resulted from the plastic deformation during the process of grinding and polishing. Ringkasan. Struktur Windmanstatten yang timbul pada logam dental Ag-Sn disebabkan oleh proses pendinginan lambat paduan tersebut dari suhu homogenisasi. Hal ini terjadi bila paduan tersebut mengandung perak atau ekivalen perak antara 75